Effectiveness of Health Education on Self-care and Self-efficacy of Patients with Coronary Heart Disease: A Systematic Review - Rita Rita; Azizah Khoiriyati; Erna Rochmawati (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Coronary heart disease is a leading cause of morbidity and mortality worldwide. Health education is needed to improve patient self-care and self-efficacy. This research aims to synthesize the literature on health education, focusing on self-care outcomes and self-efficacy among patients with coronary heart disease. A systematic review was conducted through a literature search on ScienceDirect, PubMed, Wiley Online Library, and Scopus. The search strategy used a combination of keywords with the Boolean operators